FAKTOR-FAKTOR YANG MEMENGARUHI KESEJAHTERAAN PEDAGANG DI PASAR CIHAURGEULIS BANDUNG SELAMA MASA PANDEMI COVID-19 - Muhamad Daffa Reivanza Kuswandi; Ernah Ernah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This Covid-19 pandemic has had a very significant impact on the national economy, many traders in Traditional Markets have had to experience a decrease in income during this pandemic. So that the Covid-19 pandemic has become a serious obstacle to realizing the welfare of society. This study aims to analyze the level of welfare of merchants at Cihaurgeulis Market during the Covid-19 pandemic and find out what factors affect the welfare of merchants at Cihaurgeulis Market. The research method used in this research is quantitative explanatory research. The sampling technique used is Proportionate Stratified Random Sampling with the total sample of 80 merchants. The data analysis technique used in this research are descriptive statistical analysis, welfare analysis using the proportion of food expenditure, and multiple linear regression analysis. The results showed that almost all respondents experienced a decrease in income during the pandemic with the average decline in income reached 52%. Then as many as 42 of 80 respondents belong to the category of not prosperous. The factors that affect the welfare of merchants at Cihaurgeulis Market during the pandemic are the level of education, income, the health of family members, and the ease of children entering education.